2014
DOI: 10.1007/s13593-014-0225-6
|View full text |Cite
|
Sign up to set email alerts
|

New multi-model approach gives good estimations of wheat yield under semi-arid climate in Morocco

Abstract: International audienceWheat production in Morocco is crucial for economy and food security. However, wheat production is difficult because the semi-arid climate causes very variable wheat yields. To solve this issue, we need better prediction of the impact of drought on wheat yields to adapt cropping management to the semi-arid climate. Here, we adapted the models WOFOST and CropSyst to agro-climatic conditions in Morocco. Six soft and durum wheat varieties were grown during the 2011–2012 and 2012–2013 growing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
14
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(16 citation statements)
references
References 26 publications
2
14
0
Order By: Relevance
“…This "wet soil" assumption is unrealistic for the dry regions of Europe such as the Mediterranean, especially for the case of spring crops that are sown later in the year, as we could be neglecting important soil moisture depletion happening before the start of the growing season. We can solve this issue by using soil moisture data-for instance, the ERA-Interim reanalysis product (Dee et al, 2011) The WOFOST model has been extensively used for research on crop yield and yield gap all over the world, notably in Europe (Bussay et al, 2015;Eitzinger et al, 2013;Foltescu, 2000;Kogan et al, 2013), Africa (Bregaglio et al, 2014;Kassie et al, 2014;Wolf et al, 2015), Middle East (Sargordi et al, 2013), India (Dua et al, 2013), and China (Wang et al, 2011). However, to our knowledge we are the first to apply WOFOST to estimate surface carbon exchange fluxes and to verify these against observations of GPP, TER, and NEE.…”
Section: Performance and Limits Of The Frameworkmentioning
confidence: 99%
“…This "wet soil" assumption is unrealistic for the dry regions of Europe such as the Mediterranean, especially for the case of spring crops that are sown later in the year, as we could be neglecting important soil moisture depletion happening before the start of the growing season. We can solve this issue by using soil moisture data-for instance, the ERA-Interim reanalysis product (Dee et al, 2011) The WOFOST model has been extensively used for research on crop yield and yield gap all over the world, notably in Europe (Bussay et al, 2015;Eitzinger et al, 2013;Foltescu, 2000;Kogan et al, 2013), Africa (Bregaglio et al, 2014;Kassie et al, 2014;Wolf et al, 2015), Middle East (Sargordi et al, 2013), India (Dua et al, 2013), and China (Wang et al, 2011). However, to our knowledge we are the first to apply WOFOST to estimate surface carbon exchange fluxes and to verify these against observations of GPP, TER, and NEE.…”
Section: Performance and Limits Of The Frameworkmentioning
confidence: 99%
“…Di Paola, et al [15] also, argue that misleading model validation may be caused by comparing model results with the outputs of other more general models. As uncertainties in model results related to model calibration and inputs may be high, users of these models should always refer to the conditions in which said models were developed and tested [52].…”
Section: Limitations and Advantages Of Crop Modelsmentioning
confidence: 99%
“…Sensors can acquire data remotely while being on board different platforms, such as satellites, aeroplanes, UAVs or handheld devices [52].…”
Section: Estimation Of Crop Parameters From Remote Sensingmentioning
confidence: 99%
“…Conversely, estimation of LWD is based on its relationships with meteorological variables available in standard agro-meteorological stations. Some examples of empirical LWD models are the simple relative humidity threshold model (RHM), which simulates the leaf wetness occurrence when humidity is above a threshold [10,11]; the dew point depression method (DPM), based on the principle of dew formation [12,13]; and the classification and regression tree (CART) model, which considers the non-linear relationship between leaf wetness, wind speed, rainfall, dew temperature and relative humidity in decision nodes to determine leaf wetness [14]. Kim et al demonstrated the spatial portability of the CART model through its application in different environments [15].…”
mentioning
confidence: 99%